Organization Theory and Methodology. - Jensen, Michael C. (The Accounting Review, 1983)
Abstract The foundations are being put in place for a revolution in the science of organizations. Some major analytical building blocks for the development of a theory of organizations are outlined and discussed in this paper. This development of organization theory will be hastened by increased understanding of the importance of the choice of definitions, tautologies, analytical techniques, and types of evidence. The two literatures of agency theory are briefly discussed in light of these issues. Because accounting is an integral part of the structure of every organization, the development of a theory of organizations will be closely associated with the development of a theory of accounting. This theory will explain why organizations take the form they do, why they behave as they do, and why accounting practices take the form they do. Because such positive theories as these are required for purposeful decision making, their development will provide a better scientific basis for the decisions of managers, standard-setting boards, and government regulatory bodies.